Analisis Pengaruh Kualitas Produk, Label Halal, Harga Jual Terhadap Keputusan Pembelian Konsumen Muslim (Studi Kasus Pada Cemilan Makanan Olahan UD. Rezeki Baru Kecamatan Medan Denai) - Bagus Riski; Nurlaila Harahap; M Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
This study discusses the direct influence of product quality, halal labels, and selling prices on Muslim purchasing decisions (case study on UD Rezeki Baru processed snacks, Medan Denai District). The sample in this study is Muslim consumers who make purchases at UD. Rezeki Baru, Medan Denai sub-district. The method in this study used a quantitative approach using path analysis with linear regression models supported by model tests and statistical tests using the help of SPSS version 15. From the results of research conducted, the authors conclude that this study produces a coefficient of determination (R-square) that is equal to 71.9% of the variable quality of products, halal labels, selling prices affect the purchasing decisions of Muslim consumers (case study at UD. Rezeki Baru, Medan Denai sub-district), while 19.1% is explained by other factors. Simultaneously shows the variable quality of products, halal labels, selling prices, does not affect the purchasing decisions of Muslim consumers (case study in UD. Rezeki Baru, Medan Denai sub-district), this is indicated by the calculated F value (1,133) < Ftabel (2,61). Partially shows the variable quality of products, halal labels, and selling prices affect the purchasing decisions of Muslim consumers (case study in UD. Rezeki Baru, Medan Denai sub-district).